IMPROVEMENT OF DIELECTRIC STRENGTHS FOR CROSS-LINKED POLYETHYLENE (XLPE) MEDIUM VOLTAGE CABLES - Nasrat, Loai; Ali, Mostafa; Mahmoud, Karar (International Journal of Research -GRANTHAALAYAH, 2019)
The electricity distribution companies are interested of the types of polymeric materials used in medium voltage cables which is considered the basis of power grid. In this study, it tried to enhance the electrical properties of cross-linked polyethylene (XLPE) after adding inorganic filler: such as Silica (SiO2) filler with 10%, 20%, 30% and 40% concentration percentages. The dielectric strength of the samples was tested under different thermal conditions (0, 25 and 100 C0) to simulate different types of environments. Thermal aging is simulated for one week in several temperatures (70, 100 and 120 C0) to investigate the effect of variety higher temperature stresses on the electric properties of XLPE in thermal drying oven, after adding Silica filler. Curve fitting is used to choosing the most suitable equation between dielectric strength rates under each thermal condition and variant percentages of Silica filler. It noted that the highest value of dielectric strength for XLPE can be obtained with 30% percentage of SiO2 filler [max. at 70 Co(30.07kV/mm)]. Polynomial regression by MATLAB code has been adopted to find the proper percentages of SiO2 filler and the highest value of dielectric strength. This regression algorithm is a form of linear regression where higher order powers (2nd, 3rd ..) of an independent variable are included, and it describes a relationship between an explanatory variable and a response variable.